Continuing Entomological Research During the Covid-19 Pandemic. (1st June 2021) - Boutsi, Sotiria; Campbell, Heather; Fezza, Eugenia; George, Ross; Godfrey, Cindayniah; Hoarau, Claire; Leandro, Maria; Pope, Tom; Roberts, Joe; Segar, Simon; Shaw, Jenna; Tempest, Hayden; et al.
In response to the global COVID-19 pandemic, the UK has experienced three national lockdowns and a public health campaign designed to stop the spread of the virus. The first national lockdown, starting in March 2020, led to the closure of university campuses, and laboratories having to pause practical research and move research student supervision online. During this time, laboratories had to develop way for research activities to resume whilst also complying with public health measures. The entomology group at Harper Adams University is in the Agriculture and Environment Department and forms part of the Centre for Integrated Pest Management. At present our group consists of seven staff members, ranging from early career researchers to those with over 20 years of experience in academia and industry, who collectively supervise 10 PhD students at varying stages of their research. Two of these students are completing their research at an external institute. The group carries out research across multiple sites, office buildings, research laboratories, including the Jean Jackson Entomology Laboratory (https://www.infraportal.org.uk/node/1880), as well as field and glasshouse facilities. Here we provide a narrative account of the challenges in maintaining an active research group during a year of highly restricted activities. We begin by outlining the impact that national lockdowns and public health measures had on researchers working on PhD projects through to larger UKRI and levy-funded multi-institute, multi-year projects. We address four key areas: i) maintaining productivity, ii) student-supervisor interactions, iii) accessibility and widening participation and iv) well-being and mental health. We then outline how lessons learnt from lockdown can inform best practice for a research group. Many aspects will be useful for researchers working part-time, flexible hours, remotely or at multiple sites, but we emphasise that the aim of this contribution is to share our personal experiences and not to cover every theme in what is an extremely complex set of global circumstances.